An etchant and its application, and a method for observing the bonding layer of zinc-aluminum-magnesium coating products
By using erosive agent made of nitric acid and alcohol combined with scanning electron microscope technology, the complexity and high cost of observation of zinc-aluminum-magnesium plating products is solved, and a simple and low-cost observation method is provided, suitable for steel mill applications. Clear display and process optimization of the bonding layer are achieved.
Patent Information
- Application Number
- CN202210522836.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-05-13
AI Technical Summary
The prior art cannot effectively observe the bonding layer of zinc, aluminum, magnesium plating products. The conventional methods are complex and costly, making it difficult to meet the needs of front-line technicians in steel mills.
The erosive agent made of nitric acid and alcohol has a volume concentration of 0.05%-0.4%, which is used to erode zinc-aluminum-magnesium plating products. Combined with scanning electron microscopy observation method, the sample preparation and observation process are simplified.
It provides a simple and convenient method for observing the combined layer of zinc, aluminum, magnesium plating products. It is simple to operate and low cost. It can clearly display the combined layer structure. It is suitable for front-line technicians in steel mills and helps optimize process parameters.
Smart Images

Figure CN115060566B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of steel material detection, and particularly relates to an etchant and application thereof, and a method for observing a bonding layer of a zinc-aluminum-magnesium coating product. Background Art
[0002] In the mid-1980s, with the increasing requirements for corrosion resistance of steel plates in highly corrosive environments such as construction, agriculture, and road traffic, foreign advanced steel companies have successively developed a variety of zinc-aluminum-magnesium coated steel plates with different aluminum and magnesium contents, such as Nissin Steel's ZAM products (Zn-6Al-3Mg), Nippon Steel's SuperDyma products (Zn-11Al-3Mg), JFE's Ecogal products (Zn-5Al-1Mg), etc. Since 2015, major domestic steel mills have also successively carried out industrial trial production of zinc-aluminum-magnesium products.
[0003] In the process of industrialized production of zinc-aluminum-magnesium coating products, the problem of coating bonding is bound to be encountered. At present, there are simple and convenient methods for observing the bonding layer of coating products such as GI, GA and GL. Due to the high aluminum and magnesium content of zinc-aluminum-magnesium coating products, conventional methods can no longer be used. At present, the combination of FIB and TEM is generally used. This method is complex and costly in sample preparation. It is suitable for scientific researchers, but not convenient for front-line technicians in steel plants. Summary of the invention
[0004] The purpose of the present application is to provide an etchant and its application, and a method for observing the bonding layer of a zinc-aluminum-magnesium coating product, so as to solve the problem of the lack of an etchant for zinc-aluminum-magnesium coating products.
[0005] An embodiment of the present invention provides an etchant, the components of which include nitric acid and alcohol, and the volume concentration of the nitric acid is 0.05%-0.4%.
[0006] Optionally, the alcohol is anhydrous ethanol.
[0007] Based on the same inventive concept, an embodiment of the present invention further provides an application of the above-mentioned etchant, wherein the application includes using the etchant to etch a zinc-aluminum-magnesium coating.
[0008] Based on the same inventive concept, an embodiment of the present invention further provides an application of the etchant as described above, wherein the application includes using the etchant to observe the bonding layer of a zinc-aluminum-magnesium coating product.
[0009] Optionally, the coating composition of the zinc-aluminum-magnesium coating product includes, by mass fraction, Al: 5%-20%, Mg: 2%-4%, and the rest is Zn and unavoidable impurities.
[0010] Based on the same inventive concept, an embodiment of the present invention further provides a method for observing a bonding layer of a zinc-aluminum-magnesium coating product, the method comprising:
[0011] The zinc-aluminum-magnesium coating product is sampled and pretreated to obtain a sample;
[0012] The sample is corroded and then washed to obtain an eroded sample;
[0013] The eroded sample is subjected to scanning electron microscopy to complete observation;
[0014] Wherein, the etchant used in the etch is the etchant described above.
[0015] Optionally, the erosion time is 5s-15s.
[0016] Optionally, the preprocessing includes cross-section mounting and grinding.
[0017] Optionally, the pretreatment also includes polishing and cleaning.
[0018] Optionally, the washing method is immersion, and the immersion time is 3s-5s.
[0019] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0020] The etchant provided in the embodiment of the present invention etches zinc-aluminum-magnesium coating products by combining nitric acid and alcohol, thus filling the gap of the current etchants for zinc-aluminum-magnesium coating products.
[0021] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 is a flow chart of a method provided by an embodiment of the present invention;
[0024] Figure 2 is a scanning electron microscope image provided by Example 1 of the present invention;
[0025] Figure 3is a scanning electron microscope image provided by Example 2 of the present invention;
[0026] Figure 4 This is a scanning electron microscope image provided by Comparative Example 1 of the present invention;
[0027] Figure 5 It is a scanning electron microscope image provided by Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0028] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0029] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0031] During the invention process, the applicant discovered that due to the high aluminum and magnesium content of zinc-aluminum-magnesium coating products, conventional methods can no longer be used. Currently, a method combining FIB and TEM is generally used. This method is complex and costly in sample preparation. It is suitable for scientific researchers but not convenient for front-line technical personnel in steel mills.
[0032] Therefore, a simple and convenient method for observing the bonding layer of zinc-aluminum-magnesium coating products is needed to facilitate front-line technicians in steel plants to effectively observe the quality of the bonding layer and optimize the process parameters based on the results.
[0033] The present application provides an observation method and etching liquid for the bonding layer of a medium-aluminum-zinc-aluminum-magnesium coating, so as to solve the problem that the bonding layer of a medium-aluminum-zinc-aluminum-magnesium coating cannot be clearly observed using a low-magnification scanning electron microscope. The method is simple and convenient to operate, the bonding layer presents a good visual effect, and the etching liquid is simple to prepare and has low toxicity.
[0034] The technical solution of the embodiment of the present application is to solve the above technical problems, and the overall idea is as follows:
[0035] During the invention process, the applicant discovered that due to the high aluminum and magnesium content of zinc-aluminum-magnesium coating products, conventional methods can no longer be used. Currently, a method combining FIB and TEM is generally used. This method is complex and costly in sample preparation. It is suitable for scientific researchers but not convenient for front-line technical personnel in steel mills.
[0036] Therefore, a simple and convenient method for observing the bonding layer of zinc-aluminum-magnesium coating products is needed to facilitate front-line technicians in steel plants to effectively observe the quality of the bonding layer and optimize the process parameters based on the results.
[0037] According to a typical embodiment of the present invention, an etchant is provided, wherein the etchant comprises nitric acid and alcohol, wherein the volume concentration of the nitric acid is 0.05%-0.4%, and the volume concentration of the nitric acid includes but is not limited to: 0.05%, 0.1%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35% and 0.4%. Specifically, the alcohol is anhydrous ethanol.
[0038] Controlling the volume concentration of nitric acid to 0.05%-0.4% can better show the bonding layer of zinc-aluminum-magnesium coating products. If the value is too large, it will cause excessive corrosion and the bonding layer will be invisible. If the value is too small, the corrosion will be weak and the bonding layer will also be difficult to see.
[0039] By adopting the above design, the etchant is simple to prepare and has low toxicity.
[0040] According to another typical embodiment of the present invention, there is provided an application of the above-mentioned etchant, wherein the application comprises using the etchant to etch a zinc-aluminum-magnesium coating.
[0041] According to another typical embodiment of the present invention, there is provided an application of the etchant as described above, the application comprising using the etchant to observe a bonding layer of a zinc-aluminum-magnesium coated product.
[0042] In this embodiment, the coating composition of the zinc-aluminum-magnesium coating product to which the etchant is applicable includes, by mass fraction, 5%-20% Al, 2%-4% Mg, and the rest Zn and unavoidable impurities.
[0043] According to another typical embodiment of the present invention, a method for observing a bonding layer of a zinc-aluminum-magnesium coating product is provided, the method comprising:
[0044] S1. Prepare and pretreat the zinc-aluminum-magnesium coating product to obtain a sample;
[0045] In some embodiments, preprocessing includes cross-section mounting and grinding.
[0046] Specifically, in this embodiment, the sample is processed into a size of 20mm*15mm, and then the cross section is inlaid and ground until there are no obvious visible scratches. The finer the ground surface, the better to prevent the next polishing process from taking too long and causing oxidation.
[0047] In some embodiments, pre-treatment also includes polishing and cleaning.
[0048] Specifically, in this embodiment, alcohol is used for polishing to prevent surface oxidation until the polished surface is smooth and free of scratches and stains; then the polished sample is placed with the polished surface facing up in a beaker filled with alcohol, the alcohol must at least cover the sample, ultrasonic cleaning is performed for 5-10 seconds, and then blown dry with cold air.
[0049] S2. The sample is corroded and then washed to obtain an eroded sample; wherein the erosion agent used in the erosion is the erosion agent as described above;
[0050] Specifically, in this embodiment, the alloy layer is etched by etching method, and the etching time is 5-15 seconds, and the etching time includes but is not limited to: 5 seconds, 7 seconds, 9 seconds, 11 seconds, 13 seconds and 15 seconds. After etching, the sample is immediately immersed in anhydrous ethanol for 3-5 seconds, and the anhydrous ethanol immersion time is not limited to 3 seconds, 4 seconds and 5 seconds, and then blown dry with cold air.
[0051] In some embodiments, the erosion time is 5s-15s.
[0052] Controlling the erosion time to 5s-15s can better show the bonding layer of the zinc-aluminum-magnesium coating product. If the value is too large, it will cause excessive erosion and the bonding layer will be invisible. If the value is too small, the erosion will be weak and the bonding layer will also be difficult to see.
[0053] In some embodiments, the washing method is immersion, and the immersion time is 3s-5s.
[0054] S3. Performing scanning electron microscopy on the eroded sample to complete the observation;
[0055] The eroded sample is placed under a scanning electron microscope for observation to obtain a scanning electron microscope image.
[0056] The following will describe in detail the etchant of the present application and its application, and the method for observing the bonding layer of zinc-aluminum-magnesium coating products in combination with embodiments, control examples and experimental data.
[0057] Example 1
[0058] A method for observing a bonding layer of a zinc-aluminum-magnesium coating product, the method comprising:
[0059] The sample with the coating composition of 6Al3Mg was processed into a size of 20mm*15mm, and then the cross section was inlaid and ground until there were no obvious visible scratches.
[0060] Use alcohol to polish until the polished surface is smooth and free of scratches and stains.
[0061] Place the polished sample with the polished surface facing up into a beaker filled with alcohol, with the alcohol covering the sample. Perform ultrasonic cleaning for 10 seconds, and then blow dry with cold air.
[0062] The ultrasonically cleaned sample was immersed in a nitric acid alcohol solution with a volume concentration of 0.2% for an etching time of 10 seconds.
[0063] After etching, the samples were immediately rinsed with anhydrous ethanol for 3-5 seconds and then blown dry with cold air.
[0064] The etched sample was observed under a scanning electron microscope at 5000 times magnification to obtain a clear structure of the bonding layer between the zinc-aluminum-magnesium coating and the substrate. Figure 2 shown.
[0065] Example 2
[0066] In this embodiment, the 0.2% volume concentration nitric acid alcohol solution in Example 1 is replaced by a 0.4% volume concentration nitric acid alcohol solution, and the etching time is replaced by 5 seconds. The structure of the bonding layer between the zinc-aluminum-magnesium coating and the substrate is as follows: Figure 3 As shown in the figure, it can be seen that the coating is severely corroded, an obvious step is formed between the zinc-aluminum-magnesium coating and the substrate, and the bonding layer is not clearly visible.
[0067] Comparative Example 1
[0068] In this comparative example, the 0.2% volume concentration nitric acid alcohol solution in Example 1 is replaced by a 0.001% volume concentration nitric acid alcohol solution, and the etching time is replaced by 15 seconds. The structure of the bonding layer between the zinc-aluminum-magnesium coating and the substrate is as follows: Figure 4 As shown in the figure, it can be seen that the bonding layer structure between the zinc-aluminum-magnesium coating and the substrate is not visible.
[0069] Comparative Example 2
[0070] In this comparative example, the 0.02% volume concentration nitric acid alcohol solution in Example 1 is replaced by a 0.8% volume concentration nitric acid alcohol solution, and the etching time is replaced by 5 seconds. The structure of the bonding layer between the zinc-aluminum-magnesium coating and the substrate is as follows: Figure 5 As shown in the figure, it can be seen that the coating is severely corroded, an obvious step is formed between the zinc-aluminum-magnesium coating and the substrate, and the bonding layer is not clearly visible.
[0071] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0072] (1) The observation method provided by the embodiment of the present invention is simple to operate, the visual presentation effect of the bonding layer is clear, and the quality of the bonding layer can be intuitively evaluated, which has good promotion value;
[0073] (2) The etchant provided in the embodiment of the present invention is simple and convenient to prepare, which solves the problem that the Mg element is easily corroded and affects the final effect;
[0074] (3) The observation method provided in the embodiment of the present invention is simple in sample preparation, low in cost, and highly universal, and can help front-line technicians in steel mills to quickly optimize the process and verify the effect.
[0075] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.
[0076] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0077] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. An application of an etchant, characterized in that: The components of the etchant include nitric acid and alcohol, the volume concentration of the nitric acid is 0.05%-0.4%, and the alcohol is anhydrous ethanol. The application includes using the etchant to observe the bonding layer of zinc-aluminum-magnesium plated products.
2. The use of the etching agent according to claim 1, characterized in that: The coating composition of the zinc-aluminum-magnesium coating product includes, by mass fraction, 5%-20% of Al, 2%-4% of Mg, and the rest of Zn and unavoidable impurities.
3. A method for observing the bonding layer of a zinc-aluminum-magnesium coating product, characterized in that: The method comprises: The zinc-aluminum-magnesium coating product is sampled and pretreated to obtain a sample; The sample is corroded and then washed to obtain an eroded sample; The eroded sample is subjected to scanning electron microscopy to complete observation; The components of the etching agent used in the etching include nitric acid and alcohol, the volume concentration of the nitric acid is 0.05%-0.4%, and the alcohol is anhydrous ethanol.
4. The method for observing the bonding layer of zinc-aluminum-magnesium coating products according to claim 3 is characterized in that: The erosion time is 5s-15s.
5. The method for observing the bonding layer of zinc-aluminum-magnesium coated products according to claim 3, characterized in that: The pre-processing includes cross-section mounting and grinding.
6. The method for observing the bonding layer of zinc-aluminum-magnesium coating products according to claim 3, characterized in that: The pretreatment also includes polishing and cleaning.
7. The method for observing the bonding layer of zinc-aluminum-magnesium coating products according to claim 3, characterized in that: The washing method is immersion, and the immersion time is 3s-5s.
